Egg genotyping reveals the possibility of patent Ancylostoma caninum infection in human intestine - Furtado, Luis Fernando Viana (Sci Rep, 2020)
Hookworms are intestinal parasites that cause major public health problems, especially in developing countries. To differentiate eggs from different hookworm species, it is necessary to use molecular methodologies, since the eggs are morphologically similar. Here, we performed the molecular identification of single hookworm eggs from six Brazilian states. Of the 634 eggs individually analyzed, 98.1% (622/634) represented Necator americanus, and surprisingly, 1.9% (12/634 eggs from the same patient) represented Ancylostoma caninum. DNA analysis of the A. caninum-positive stool sample revealed no contamination with animal feces. This is the first report of the presence of A. caninum eggs in human feces, which may have a direct implication for the epidemiology of hookworm infection caused by this species. This suggests the need for special attention regarding prophylaxis, as different reservoirs, previously not described, may have great relevance for the spread of A. caninum.